PENGGUNAAN PEMODELAN SUMBER PLASMA HELIUM PADA KEADAAN SETIMBANG UNTUK APLIKASI PLAK GIGI - Nandita Devira; Toto Saktioto (Komunikasi Fisika Indonesia, 2022)
Helium plasma source modelling was performed in order to obtain species density at balanced conditions under pressure of 1 atm. The software used in this modelling is matrix laboratory software (MATLAB). The equation used is a continuity equation that depends on the position and parameters of Arrhenius. Plasma temperatures used were 0.1 eV, 0.2 eV, 0.3 eV, and 0.5 eV. Species involved in a plasma consist of electrons, He, He+, He2+, He*, and He2*. The modelling results showed that the density value of He species increases as temperature increases. It is noted that the obtained the density of He (nHe) when reaching a balanced condition at the temperature  of T = 0.1, 0.2, 0.3, and 0.5 are 3.0137 × 1025, 7.9506 × 1026, nHe = 1.6489 × 1028, and 7.1384 × 1029, respectively. This is because He is a noble gas that is monatomic and chemically inert. Thus resulting in stable plasma production and gaining an increase in density value. Plasma-charged species are the main media that cause the disinfection of microorganisms because they can break the hydrogen bond of the organic molecules that make up the dental plaque. So the influence of charged species when applied to dental plaque has more effective than that of neutral reactive species.